2018
DOI: 10.3390/rs10030388
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Rainfall (TRMM 3B42-V7) Performance Assessment and Adjustment over Pahang River Basin, Malaysia

Abstract: Abstract:The Tropical Rainfall Measuring Mission (TRMM) was the first Earth Science mission dedicated to studying tropical and subtropical rainfall. Up until now, there is still limited knowledge on the accuracy of the version 7 research product TRMM 3B42-V7 despite having the advantage of a high temporal resolution and large spatial coverage over oceans and land. This is particularly the case in tropical regions in Asia. The objective of this study is therefore to analyze the performance of rainfall estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…However, the SRPs showed poor performance in simulating daily rainfall. The authors of [72] also found that by applying bias correction on SRPs, the error discrepancy and correlation between TRMM and rain gauge can be reduced by 18.38% and up to 16.28% respectively. Improving the accuracy of SRPs by considering bias correction is of great importance to ensure their applicability for daily and/or hourly application in hydrological and water resources modelling.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the SRPs showed poor performance in simulating daily rainfall. The authors of [72] also found that by applying bias correction on SRPs, the error discrepancy and correlation between TRMM and rain gauge can be reduced by 18.38% and up to 16.28% respectively. Improving the accuracy of SRPs by considering bias correction is of great importance to ensure their applicability for daily and/or hourly application in hydrological and water resources modelling.…”
Section: Resultsmentioning
confidence: 96%
“…It is unanticipated, in particular, the GSMaP-NRT data, as studies found that GSMaP had a significant discrepancy with observed data in rainfall estimation [68][69][70] and runoff simulation [71]. In Malaysia, rainfall estimates using SRPs have been carried out in several studies [19,20,72]. It has been reported that all SRPs are able to produce good results in estimating annual and monthly precipitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this adjustment, Delahaye [8] showed many qualitative (hit or miss of rainy events) and quantitative estimation errors in 3B42 version 6 in the Brazilian Legal Amazon. These errors partially arise due to a lower capacity of multi-satellite based algorithms-such as those used by TRMM-to detect warm top stratiform cloud systems [11][12][13] particularly in mountainous regions, where precipitations tend to be underestimated [14,15]. Still, 3B42 generally shows high performance, if not the best, compared to other remote sensing products [8,13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, numerous studies have been carried out to validate the TRMM precipitation product in different regions [15][16][17][18][19][20]. Tong et al evaluated four widely used global high-resolution satellite precipitation products against gauge streamflow observations over the Tibetan Plateau [21].…”
Section: Introductionmentioning
confidence: 99%